Contour map of nano-mechanical-properties using Isostatic Pressing. (August 2017) - Feng, G.; Qin, H.L.; Jia, Y.H.; Zhao, L.; Zou, Y.M.; Wang, S.B.; Wang, H.Z.
Abstract: The in-situ mechanical property is the most important data when simulating, designing structural materials[1] . We propose a high-resolution crystal plasticity approach that utilizes continuous indentation measurement enabled by Isostatic Pressing. The mechanical property of the microstructures can be associated with the collapse deformation. Compared with conventional hardness-test, this approach is inherently performed on the continuous contact area that can overcome the surface pileup, sink-in for the calculation of hardness and modulus, whilst it is time saving, high-throughput. Additionally, with statistical investigation of Isostatic Pressing Contour Map, mechanical property can also be non-destructive characterized on multiple-scale. Graphical abstract: Highlights: Isostatic Pressing Contour Map is non-destructive. Ensure strong bonding with the elastoplastic properties and hardness; Unpredictable pileup, sink-in in the contact area can be overcome; The mechanical features can be high-throughput statistical analyzed on nano-scale.